Evaluation of caregivers' burden of the patients receiving home health service in Manisa - Çağlar Sögüt; Pınar Erbay Dündar (Turkish Society of Public Health Specialists, 2017)
Objective: The aim of this study is to evaluate the caregivers' burden and relevant factors who look after patients that receive home health service. Method: This cross-sectional study is conducted caregivers who look after home health service patients in years 2014-2016 in Manisa Şehzadeler. The study consists of 234 individuals. The participation rate is 83.5 %. A questionnaire which consists of sociodemographic factors, questions about the illness and Zarit Caregiver Burden Scale that evaluates caregivers' stress is applied to participants. Results: 67.7 % of caregivers have mild/ moderate/ severe burden, 87.4 % of them are women, 67.1 % of them are first degree relatives and 89.8 % of them are members of lower social class. Having the caregiver in the lower social class, having the patient's daughter-in-law, extended family structure and patient's bad health perception are the reasons that increase the caregiver's burden. Conclusion: 67.7 % of caregivers have mild/ moderate/ severe burden. Caregivers need to be supperted economically, socially and psychologically. It is also suggested that paid caregivers who cares patients at home should be promoted and additional studies should be carried out.